Eosinophilic recruitment in thermally injured older animals is associated with worse outcomes and higher conversion to full thickness burn. Issue 5 (August 2020) - Jackson, Kianna R.; Pollins, Alonda C.; Assi, Patrick E.; Kassis, Salam K.; Cardwell, Nancy L.; Thayer, Wesley P.
Highlights: Older mice are more likely to convert from partial to full thickness burn injury. Localized EOTAXIN expression is increased in both old and young mice after burn. Older mice have elevated baseline levels of systemic EOTAXIN. Eosinophil populations are elevated in the burns of older mice as compared to young. Abstract: Background: Partial burn injury in older patients is associated with higher rates of morbidity, mortality, and conversion to full thickness burn (Finnerty et al., 2009; Pham et al., 2009). Both human and mouse models demonstrate an altered systemic immune response in older subjects, however less is known about the localized response (Jeschke et al., 2016; Farinas et al., 2018; Mohs et al., 2017). We hypothesized that a mouse model could demonstrate differences in the localized inflammatory response of the old. Methods: Six old (66 weeks) and young (8 weeks) mice received partial thickness thermal burns. Localized and systemic expression of nine chemokines (TNFalpha, MCP-1, MIP-2, S100A9, EGF, IL-10, RANTES, G-CSF, and EOTAXIN) were evaluated at day 3 after burn using Luminex analysis. Vimentin immunostaining was used to evaluate injury depth. Results: Vimentin staining demonstrated increased burn depth in old mice (449 ± 38 μm) as compared to young (166 ± 18 μm) (p < 0.05). Both groups exhibited increased localized expression of EOTAXIN after burn (p < 0.05), however expression in old mice (83.6 ± 6.1 pg/ml) was lower than that of young (126.8 ± 18.7 pg/ml) (p < 0.05). Systemically, however, old mice had increased baseline EOTAXIN expression (1332.40 ± 110.78 pg/ml) compared to young (666.12 ± 45.8 pg/ml) (p < 0.005). Conclusions: EOTAXIN is one of the primary chemoattractants for selective eosinophilic recruitment and activation. While eosinophils are important for wound healing, a hyperactive eosinophilic response can result in tissue damage. We hypothesize that the increased baseline serum EOTAXIN in the old may prime their hyperactive response, and may contribute to their worse clinical outcomes. Long-term eosinophil activation requires further study, however our findings indicate a role for EOTAXIN and eosinophils in burn response.